Strengthening Character Education through Role Models Educators - Novita Sariani; Yoga Prasetya Adi Nugraha (Manunggal Halim Jaya, 2026)
Education character is focus main in education in Indonesia. The role of educator as role model can in a way effective strengthen education character students. Lack of role model from part educators, good in speech, attitude, and action everyday, making student No own role model real For imitated . Its implementation No only through delivery material lessons, but Also through customs, culture school, and role model educators. Articles This aim For research role educator in strengthen education character through role model. Method studies literature covering focus, keywords, collection sources, selection, classification, analysis, synthesis, and discussion. Results review literature show that educator own position strategic as capable role models form attitudes, behavior, and morals of students. Education character is runway important For form personality student so that they own moral values, ethics, and attitude positive in life. Role model educator play role strategic in the process of strengthening education characters in the environment school. Through attitude, speech, behavior, and action, educator become role model imitated real and internalized by student.